Diet enriched with high-phenolic cocoa potentiates hippocampal brain-derived neurotrophic factor expression and neurogenesis in healthy adult micewith subtle effects on memory - Melgar-Locatelli, Sonia; Mañas-Padilla, María del Carmen; Castro-Zavala, Adriana; Rivera-González, Patricia; Razola-Díaz, María del Carmen; Monje, Francisco J; Rodríguez-Pérez, Celia; Castilla-Ortega, María Estela; Razola-Díaz (Royal Society of Chemistry, 2024)
Cocoa is widely known for its health benefits, but its neurocognitive impact remains underexplored. This preclinical study aimed to investigate the effects of cocoa and cocoa polyphenols on hippocampal neuroplasticity, cognitive function and emotional behavior. Seventy young-adult C57BL/6JRj male and female mice were fed either a standard diet (CTR) or a diet enriched with 10% high-phenolic content cocoa (HPC) or low-phenolic content cocoa (LPC) for at least four weeks. In a first experiment, behavioral tests assessing exploratory behavior, emotional responses and hippocampal-dependent memory were conducted four weeks into the diet, followed by animal sacrifice a week later. Adult hippocampal neurogenesis and brain-derived neurotrophic factor (BDNF) expression in the hippocampus and prefrontal cortex were evaluated using immunohistochemistry and western blot. In a different experiment, hippocampal synaptic response, long-term potentiation and presynaptic-dependent short-term plasticity were studied by electrophysiology. Cocoa-enriched diets had minimal effects on exploratory activity and anxiety-like behavior, except for reduced locomotion in the LPC group. Only the HPC diet enhanced object recognition memory, while place recognition memory and spatial navigation remained unaffected. The HPC diet also increased adult hippocampal neurogenesis, boosting the proliferation, survival and number of young adult-born neurons. However, both cocoa-enriched diets increased immobility in the forced swimming test and hippocampal BDNF expression. Hippocampal electrophysiology revealed no alterations in neuroplasticity among diets. The results were mostly unaffected by sex. Overall, the HPC diet demonstrated greater potential regarding cognitive and neuroplastic benefits, suggesting a key role of cocoa flavanols in dietary interventions aimed at enhancing brain health.
Keywords: Cacao - Propiedades; Cocoa-enriched diets; Cognitive function; Emotional behavior; Polyphenols; Adult hippocampal neurogenesis; Brain plasticity